2014
DOI: 10.1088/0004-637x/788/2/144
|View full text |Cite
|
Sign up to set email alerts
|

RECONSTRUCTING THE STELLAR MASS DISTRIBUTIONS OF GALAXIES USING S4G IRAC 3.6 AND 4.5 μm IMAGES. II. THE CONVERSION FROM LIGHT TO MASS

Abstract: We present a new approach for estimating the 3.6 µm stellar mass-to-light ratio Υ 3.6 in terms of the [3.6]-[4.5] colors of old stellar populations. Our approach avoids several of the largest sources of uncertainty in existing techniques using population synthesis models. By focusing on mid-IR wavelengths, we gain a virtually dust extinction-free tracer of the old stars, avoiding the need to adopt a dust model to correctly interpret optical or optical/NIR colors normally leveraged to assign the mass-to-light r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
268
5
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(316 citation statements)
references
References 62 publications
(95 reference statements)
41
268
5
2
Order By: Relevance
“…Bulge luminosities 9 (Table 1) from Paper Iwere converted into stellar masses using a constant 3.6 m m mass-to-light ratio, 0.6 3.6 G = (Meidt et al 2014). We additionally explored a more sophisticated way to compute mass-to-light ratios, using the color-3.6 G relation published by Meidt et al (2014), their Equation (4)), which allows one to estimate 3.6 G of a galaxy from its Table 1) when available for our galaxies, or were estimated from the bulge stellar velocity dispersion, σ, using the color-σ relation presented by Peletier et al (2012, their Figure 6).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Bulge luminosities 9 (Table 1) from Paper Iwere converted into stellar masses using a constant 3.6 m m mass-to-light ratio, 0.6 3.6 G = (Meidt et al 2014). We additionally explored a more sophisticated way to compute mass-to-light ratios, using the color-3.6 G relation published by Meidt et al (2014), their Equation (4)), which allows one to estimate 3.6 G of a galaxy from its Table 1) when available for our galaxies, or were estimated from the bulge stellar velocity dispersion, σ, using the color-σ relation presented by Peletier et al (2012, their Figure 6).…”
Section: Datamentioning
confidence: 99%
“…We additionally explored a more sophisticated way to compute mass-to-light ratios, using the color-3.6 G relation published by Meidt et al (2014), their Equation (4)), which allows one to estimate 3.6 G of a galaxy from its Table 1) when available for our galaxies, or were estimated from the bulge stellar velocity dispersion, σ, using the color-σ relation presented by Peletier et al (2012, their Figure 6). We found that the range in [3.6]-[4.5] color is small (0.06 mag), and thus the range in 3.6 G is also small (0.04).…”
Section: Datamentioning
confidence: 99%
“…Velocity fields of these types of galaxies are rich with information that are worth investigating. Furthermore, as resolved SPS models as in Zibetti et al (2009), Corbelli et al (2014, Meidt et al (2014), and Rahmani et al (2016) are in their early stages, derivations of many more stellar density maps is strongly encouraged to be able to quantify the asymmetries of the gravitational potential of stellar disks directly. This is more straightforward for the gas component since atomic and molecular surface density maps are routinely acquired with mm and cm arrays.…”
Section: Discussionmentioning
confidence: 99%
“…Under this assumption, McGaugh & Schombert (2013) found a mean value of (0.5 ± 0.1) M /L ,3.6 µm in disk galaxies. Meidt et al (2014) constrained the mean value to 0.6 M /L ,3.6 µm . The mass-to-light ratio at 4.5 µm should be similar or even less than the massto-light ratio at 3.6 µm (Oh et al 2008).…”
Section: Mass Profile Of the Clustermentioning
confidence: 99%